Exploring Civil Engineers’ Entrepreneurial Competence In South Africa - Polycarpe Feussi; Charles Mbohwa; Marcus Dlamini (International Journal of Entrepreneurship, Business, and Creative Economy, 2025)
This study examines the entrepreneurial aptitude of civil engineers in South Africa by surveying 340 engineers from the South African Institution of Civil Engineering (SAICE). Given the economic and technological changes in the engineering sector, it is crucial to understand the entrepreneurial skills of civil engineers to encourage innovation and enhance industry competitiveness. The research was undertaken using a quantitative cross-sectional method to collect data randomly from 374 individuals among over 10,000 registered engineers, ensuring a representative sample of the larger population. The research employed a structured questionnaire to assess entrepreneurial competence in areas such as identifying opportunities, evaluating risks, managing resources, and strategic thinking. Statistical analysis is used to gauge levels of entrepreneurial skills and identify factors that impact these competencies. The outcomes reveal varied entrepreneurial capabilities among civil engineers, with strengths in opportunity recognition and resource mobilisation but challenges in risk management and strategic planning. These results emphasize the need for tailored training and development programs to enhance entrepreneurial skills in the civil engineering field. The study contributes to the discourse on the role of civil engineers as innovators in the construction industry, highlighting the significance of integrating entrepreneurial education into engineering curricula and professional development initiatives. By equipping engineers with robust entrepreneurial capabilities, the industry can navigate complexities more effectively and drive sustainable growth in South Africa.